2009
DOI: 10.1534/genetics.109.101386
|View full text |Cite
|
Sign up to set email alerts
|

The Multi-AT-Hook Chromosomal Protein of Drosophila melanogaster, D1, Is Dispensable for Viability

Abstract: The D1 protein is a high mobility group A (HMGA)-like nonhistone chromosomal protein with primary localization to certain AT-rich satellite DNA sequences within heterochromatin. The binding of D1 to euchromatic sequences is less studied and the functional significance of its chromosomal associations is unclear. By taking advantage of existing P-insertion alleles of the D1 gene, I generated D1 null mutations to investigate the phenotypic effect of loss of the D1 gene. In contrast to a previous report, I determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…We have previously shown that D1-null flies are viable and fertile and do not exhibit any obvious phenotypic abnormalities (Weiler and Chatterjee 2009). We also determined that although the D1 protein localizes to heterochromatin, D1 mutants are not modifiers of position effect variegation.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…We have previously shown that D1-null flies are viable and fertile and do not exhibit any obvious phenotypic abnormalities (Weiler and Chatterjee 2009). We also determined that although the D1 protein localizes to heterochromatin, D1 mutants are not modifiers of position effect variegation.…”
Section: Discussionmentioning
confidence: 71%
“…Similar to mammalian HMGA proteins (Fusco and Fedele 2007), Drosophila D1 is not essential for viability. D1-null animals were fertile and did not exhibit any obvious phenotypes that would illuminate the cellular role of the D1 protein (Weiler and Chatterjee 2009). This result indicates that there is redundancy to D1 function.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations